Zina: Kur’an ve Demokratik Kongo Cumhuriyeti’nin ceza hukuku karşılaştırılması - Kazadı, Mwamba (My University, 2017)
ÖZETZina suçu ailenin doğal temellerinde meydana gelen bozulmalar karşısında toplumun hissettiği tedirginliği ifade eder. Ne zaman ki bir kimsenin bir kadınla cinsel ilişkiye girilirse, ailevi yükümlülük ve ödevler ihlal edilmiş olur. Zina günümüzde artık eski toplumlarda olduğu gibi ölüm ces the uneasiness felt by the society in the face of the distortions that occur in the natural foundation of the family. Whenever a person is in sexual intercourse with a woman, family responsibilities and duties will be breached. Adultery is no longer considered today as the most serious offenses punishable by death, as in the old society. Therefore, besides the Qur'an, if the Congolese criminal law is in conflict with the social order, the sanctions that are anticipated against the diversity and multiplicity of sexual deviations are questioned.
Keywords: adultery; ceza hukuk; Congo; crime; criminal law; Dini yönler; Hukuk; Hukuki yönler; İslam; İslam dini; Kongo; Kur’an; Qur'an; sanction; suç; yaptırım; Zina